2021
DOI: 10.1186/s13287-021-02602-4
|View full text |Cite
|
Sign up to set email alerts
|

sTNFRII-Fc modification protects human UC-MSCs against apoptosis/autophagy induced by TNF-α and enhances their efficacy in alleviating inflammatory arthritis

Abstract: Background Tumor necrosis factor (TNF)-α inhibitors represented by Etanercept (a fusion protein containing soluble TNF receptor II (sTNFRII) and the Fc segment of human IgG1) play a pivotal role in Rheumatoid arthritis (RA) treatment. However, long-term use increases the risk of infection and tumors for their systemic inhibition of TNF-α, which disrupts the regular physiological function of this molecular. Mesenchymal stem cells (MSCs)-based delivery system provides new options for RA treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…MSCs can differentiate into chondrocytes and induce the resident progenitor cells differentiation, and secret lots of cytokines to promote cartilage regeneration [38,39]. However, the chondrogenic differentiation of MSCs in vivo is instable and susceptible to the microenvironment [15,34]. The component of OA SF is complicated and may have a potential effect on chondrogenesis of MSCs, there study have showed the catabolic factors such as IL-1 or TNF-α in OA SF inhibit chondrogenesis of MSCs, but blocking IL-1 or TNF-α just partially overcame the inhibitory effect [40], which indicates that there are additional factors present in OA SF that participate in inhibition of MSCs chondrogenic differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MSCs can differentiate into chondrocytes and induce the resident progenitor cells differentiation, and secret lots of cytokines to promote cartilage regeneration [38,39]. However, the chondrogenic differentiation of MSCs in vivo is instable and susceptible to the microenvironment [15,34]. The component of OA SF is complicated and may have a potential effect on chondrogenesis of MSCs, there study have showed the catabolic factors such as IL-1 or TNF-α in OA SF inhibit chondrogenesis of MSCs, but blocking IL-1 or TNF-α just partially overcame the inhibitory effect [40], which indicates that there are additional factors present in OA SF that participate in inhibition of MSCs chondrogenic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Brie y, chondrocyte spheroids were treated with 8 M guanidine HCL containing 0.05 M acetate, pH 5.8 and proteinase inhibitors overnight. Then, the absorbance of eluent was measured at 600 nm using a microplate reader as previously described [15].…”
Section: Alcian Blue Stainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice with defects in FASL or TNF signaling are protected against arthritis induced by immunization with xenogeneic type II collagen in complete Freund's adjuvant [911][912][913][914]. Similar protection was observed in mice transplanted with mesenchymal stem cells engineered to express TNF inhibitors [915]. In keeping with this evidence, the myeloid cell specific deletion of Fas or the administration of antibodies that target both TNF and chemokine (C-X-C motif) ligand 10 (CXCL10) resulted in accelerated disease resolution in a model of rheumatoid arthritis induced by K/BxN serum transfer [916,917].…”
Section: Autoimmune and Inflammatory Diseasesmentioning
confidence: 94%
“…Similarly, 20 ng/ml TNF-α stimulation of human umbilical cord MSCs for 24 h increased the expression of autophagy-related protein microtubule-associated protein 1 light chain B-II (LC3B-II) and lowered the expression of autophagy inhibitory molecule tribbles homology protein 3 (TRIB3) ( 15 ). Therefore, in the inflammatory microenvironment, and especially during in vitro experiments, the presence of high concentrations of inflammatory factors promotes the survival of MSCs via autophagy.…”
Section: Tnf-α Inhibits Msc Proliferation While Promoting Their Autop...mentioning
confidence: 99%